Protecting Inuit Language and Culture in Inuit Nunangat: Taking Agency to Decolonize Education - MacDonald, Natasha (Études Inuit Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2024)
Decolonizing education is crucial for Inuit communities, given the enduring impact of Canadian government policies on our language and culture through colonization. In a globalized world, Inuit must take action to reverse language loss and language shift. This examination provides Inuit insights of Inuit colonization context for education leaders in Inuit Nunangat and beyond. It underscores the far-reaching effects of colonialism on education and the urgent need to address resulting educational and socioeconomic disparities. This commentary outlines strategies for decolonizing education systems, focuses on revitalizing and preserving language and culture, and shares examples of how some communities have already begun the process. Inuit language and culture can achieve vitality when interwoven with Inuit Qaujimajatuqangit (traditional Inuit knowledge), traditional activities, and land-based practices. Schools can facilitate this by implementing culturally responsive pedagogy and the inclusion of Elders, ensuring a holistic approach to education.